PLANTS AS ECOTOUR ATTRACTIONS AROUND TRAIL OF MANGROVE INFORMATION CENTRE IN MANGROVE FOREST OF SOUTHERN BALI - Sugi Wahyuni, I G. A.; Ardhana, I P. G.; Sudirga, S. K.; Ginantra, I K. (Bumi Lestari; Vol 5 No 2, 2012)
A study on plants species sighted around mangrove information centre ofNgurah Rai Mangrove Forest (Tahura Ngurah Rai), Sothern of Bali province(Indonesia), was undertaken in March 2004. The plants sighted on both sides of themangrove trail were listed. Their potential as ecotour attractions was then identified.Results of the study showed that there were 42 plant species identified aroundmangrove trail of this forest. Twelve mangrove species in this ecosystem may act asmajor attractions to the tourists doing tracking there. Information on protected species,the potential use of plants for humans, such as for animal fodder, medicine, the use inancient Balinese community, in traditional way of life of Balinese which is last untilnow, the use for offering in Hindu’s ceremony may also be interesting for tourists.Some plant species may cause problems to tourists who doing trekking so needprecaution, including on those which cause bleeding and disturbance to humanbreathing.
Keywords: plants, tourist attraction, mangrove